The transition of post-Soviet-type economies: expected and unexpected developments - WINIECKI, J. (PSL Quarterly Review, 2013)
The transition of former Soviet-type countries has spawned a growing literature with debates taking shape on “shock therapy” versus the gradualist approach, the sequencing of transition measures, choice of privatisation methods, etc. The present work looks at what is missing in this avalanche of articles and papers: an attempt at stock-taking. The author looks at theorists’ concerns from two different angles: first, whether certain developments expected by theorists did or did not happen and, second, whether certain developments that happened were expected by theorists. One of the most important insights provided is that only a small part of theorists’ expectations about problems of transition did, in fact, materialise in an manner expected by theory. JEL: P20, P26